Adsorption of Methylene Blue by Low-Cost Biochar Derived from Elephant Dung - Suma, Yanasinee; Pasukphun, Nittaya; Eaktasang , Numfon (Applied Environmental Research, 2021)
Elephant dung biochar (ED350) prepared by controlled heating at 350 ºC was used to adsorb methylene blue (MB) in an aqueous solution. The effects of adsorption time, pH, adsorbent dosage, and initial MB concentration were examined. Kinetic, isotherm, and thermo-dynamic models were then further analyzed to determine the adsorption. The results show that ED350 was found to be efficient within 180 min. The optimum pH of MB adsorption was 11. The Langmuir isotherm model was found to be the most suitable fit for the adsorption equilibrium data, with ED350 having a homogeneous surface. The calculated equilibrium parameter (RL) values were greater than zero and less than one, indicating a favorable adsorption process and that ED350 was an efficient adsorbent for MB removal. The kinetics of MB adsorption onto ED350 obeys the pseudo-second-order model. The results of thermo-dynamic data consideration reveal that the adsorption process is spontaneous and exothermic in nature. This finding suggests that ED350 may prove to be an efficient low-cost adsorbent of MB from wastewater.